PKM PELATIHAN PENINGKATAN PENGETAHUAN DAN KEMAMPUAN KADER DALAM MENGENAL TUMBUH KEMBANG BALITA DI DESA NAUMBAI KECAMATAN KAMPAR KABUPATEN KAMPAR - Kasumayanti, Erma; Hotna Siagian, Siti (COVIT (Community Service of Tambusai), 2022)
Monitoring the growth and development of children is important to be done early to find out any disturbances and delays in the child’s growth. Children who experience growth and development that are not optimal can cause disturbances in the development of physical organs, psychological, emotional intelligence and social intelligence in children. Efforts to improve children’s health status are carried out by comprehensive and quality guidance and monitoring of child growth and development by organizing child growth and development stimulation and early intervention activities (SDIDTK). These activities are carried out in a comprehensive and coordinated manner which are held in the form of partnerships between families, communities (posyandu cadres) and professionals as well as policies according to the implementation of the SDIDTK program. In Naumbai Village, Kampar District, it is known that some cadres have never received training on child growth and development, but all posyandu cadres have received training in filling out the MCH handbook, posyandu cadres do not explain the progress and setbacks of growth and development to parents due to lack of knowledge and ability of cadres in detecting child growth and development.Training to increase knowledge and abilities for posyandu cadres can help monitor children’s growth and development so that it can be seen if there are problems with child development. This activity begins with the preparation, implementation and evaluation stages of activities. After training for cadres on December 20, 2021, it was found that there was an increase in cadre knowledge about SDIDTK education and on average cadres were able to practice SDIDTK using the KPSP instrument properly. It is expected for cadres to be able to apply the knowledge and skills acquired in monitoring the growth and development of children so that the progress or decline of children can be monitored optimally. Keywords: Improving knowledge of posyandu cadres, growth and development of infants and toddlers.